Digital Community Development: Media Pelestarian Kearifan Lokal Wisata Jurang Toleh Kabupaten Malang - Sri Widayati; Muhammad Hanif Fahmi; Lian Agustina Setiyaningsih; Aryo Prakoso Wibowo (Universitas Merdeka Malang, 2021)
The global challenge in preserving local wisdom is be in the event of social adjustment to technology adoption. Communities and groups can accelerate the use of technology to preserve local wisdom. Jatiguwi, through Jurang Toleh Park, has become a pilot project in digitally empowering communities to carry out local wisdom and improve the economy of rural communities. This study used a qualitative descriptive method involving four informants based on the following criteria: involvement village activities, actively participating village activities, and being involved village tourism activities. The sampling technique used was purposive sampling, data analysis technique used Miles and Huberman's analysis. This research emphasizes on digital empowerment efforts for the community to preserve local wisdom and strengthen the village economy. The result of this research is that the success of digital empowerment starts with digital understanding by the community. Then involvement in developing tourism potential, visitor management of tourism and tourism promotion. These four things are realized through independent training by the community.Keywords: Digital Community Development, Local Wisdom, Empowerment MediaDOI : https://doi.org/10.26905/nomosleca.v7i1.5490